Contact loss between railway track and subgrade in vertical plane during roadbed research - Bednarek, Wołodzimierz; Laurinavičius, Alfredas (Journal of Civil Engineering and Management, 2003)
In the paper a new method of railway subgrade investigation is analysed. Contact loss between track and subgrade in vertical plane is considered. During the roadbed investigations the rail is jacked up using a plate called “VSS”. It is assumed that variable temperatures have influence on the rail which is laid on a curved roadbed. Elasticity of the railway roadbed is calculated. Finally formulas and dependences of various types of track structures are obtained.First Published Online: 26 Jul 2012